The location of the United States' FDI under the share gravity model - de Mello-Sampayo, F. (International Economic Journal, 2007)
This paper examines the geographical distribution of US MNEs FDI using the share gravity model, which adds a competition factor to the classical gravity formulation. The aim is to show that, unlike previous applications of the gravity model to FDI, the share of FDI pertaining to a location is determined not only by its own characteristics but also by those of competing locations. A dynamic share gravity model is estimated for a panel of both industrialised and developing countries using five alternative measures of FDI. The results vindicate the superiority of the share relative to the classical version of the gravity model in that the competition factor has a significantly negative impact on the FDI share.